Genetics of Ataxias in Indian Population: A Collative Insight from a Common Genetic Screening Tool. Issue 2 (10th March 2022) - Sharma, Pooja; Sonakar, Akhilesh Kumar; Tyagi, Nishu; Suroliya, Varun; Kumar, Manish; Kutum, Rintu; Asokchandran, Vivekananda; Ambawat, Sakshi; Shamim, Uzma; Anand, Avni; Ahmad, Ishtaq; Shakya, Sunil; et al.
Abstract: Cerebellar ataxias (CAs) represent a group of autosomal dominant and recessive neurodegenerative disorders affecting cerebellum with or without spinal cord. Overall, CAs have preponderance for tandem nucleotide repeat expansions as an etiological factor (10 TREs explain nearly 30–40% of ataxia cohort globally). The experience of 10 years of common genetic ataxia subtypes for ≈5600 patients' referrals (Pan‐India) received at a single center is shared herein. Frequencies (in %, n) of SCA types and FRDA in the sample cohort are observed as follows: SCA12 (8.6%, 490); SCA2 (8.5%, 482); SCA1 (4.8%, 272); SCA3 (2%, 113); SCA7 (0.5%, 28); SCA6 (0.1%, 05); SCA17 (0.1%, 05), and FRDA (2.2%, 127). A significant amount of variability in TRE lengths at each locus is observed, we noted presence of biallelic expansion, co‐occurrence of SCA‐subtypes, and the presence of premutable normal alleles. The frequency of mutated GAA‐FRDA allele in healthy controls is 1/158 (0.63%), thus an expected FRDA prevalence of 1:100 000 persons. The data of this study are relevant not only for clinical decision making but also for guidance in direction of genetic investigations, transancestral comparison of genotypes, and lastly provide insight for policy decision for the consideration of SCAs under rare disease category. Abstract : Sharma et al. share experience from cerebellar ataxia (CA) investigations linked to trinucleotide repeat expansion mutations in the largest cohort from India. The occurrence of CA subtypes is under‐reported than actual known data to the health care settings. Therefore, the prevalence of CA mutations along with various other related aspects is assessed.